Concomitant surgical ablation of atrial fibrillation: long-term outcomes. (25th November 2020) - Muneretto, C; Baudo, M; Petruccelli, R; Stara, A; Moscatiello, M; Rosati, F; Benussi, S
Abstract: Introduction: Atrial fibrillation (AF) is the most common cardiac related arrhythmia, independently associated with an increased risk of death and high level of morbidity, such as stroke, heart failure, as well as frequent hospitalization and reduced quality of life. Surgical ablation is an effective therapy for patients with AF undergoing concomitant cardiac surgery. Purpose: In this study we report the results of concomitant surgical AF ablation, in terms of efficacy and safety, with a long-term follow-up at 10 years. Methods: Two-hundred fourteen (214) consecutive patients (female, 45.17%) underwent from 1999 to 2016 surgical ablation of AF concomitantly with other major cardiac procedures. Mean age was 67.4±9.82. Patients had persistent and long-standing persistent AF in 64.65% of cases. Primary endpoints were overall survival, freedom from stroke and freedom from AF. Results: Perioperative mortality was 2.3% (5/214). Mean EuroSCORE II was 5.2±4.4. Concomitant mitral valve surgery was performed in 56.74% of patients, 31% of patients had a concomitant aortic valve surgery, while myocardial revascularization either isolated or associated with aortic valve was performed in 11.63% and 3.72% of cases respectively. Ablation was carried out by means radio-frequency box lesions set in 35.51% (76/214) of patients while pulmonary veins isolation with bipolar clamp and Cox-MAZE IV was performed in 51.86% (111/214) and 12.61% (27/214) of patients respectively. Left atrial appendage (LAA) exclusion was performed in 57 patients (26.51%) after careful echocardiographic investigation of diastolic and atrial function. Incidence of early postoperative (30 days) permanent pacemaker implantation was as low as 2.3%. The mean follow-up was 6.71±4.47 years. The New York Heart Association functional class (2.84 vs. 1.91, p<0.001) and ejection fraction (54.4% vs. 56.6%, p<0.001) were improved compared with the preoperative status. At 10 years Kaplan-Meier overall survival was 62.3%. Freedom from cardiac related death was 98%, while freedom from stroke was 98% at 10 years. Efficacy endpoint showed a freedom from AF at 10 years, according to HRS criteria of 66.7%. Fisher exact test comparing mitral surgery patients or ischemic CABG-patients showed no differences in terms of stroke rate (p=0.999), while postoperatively, there was a higher rate of stroke at thirty days in patients with postoperative AF (p=0.019). Conclusions: Concomitant surgical ablation of AF was associated with a very low incidence of postoperative PM implantation and provides excellent results in terms of stable rhythm outcome at long-term. Postoperative AF significantly increased the risk of stroke in the early postoperative period. Funding Acknowledgement: Type of funding source: None